(untitled) (Communications in Inorganic Synthesis, 2016)
Two new Ni(II) complexes based on pyridine-2,4,6-tricarboxylic acid had been synthesized and characterized by elemental analysis, IR spectrum and single-crystal X-ray diffraction analysis. TGA curves show that these two complexes first removes water molecules , and then the ligand split for complexes 1 and 2, and the remained residue is NiO.